Effects of Inorganic Zn and Cu Supplementation on Gut Health in Broiler Chickens Challenged With Eimeria spp. - Santos, Tatiane Souza dos; Teng, Po-Yun; Yadav, Sudhir; Castro, Fernanda Lima de Souza; Gould, Rebecca Lizabeth; Craig, Steven Wesley; Chen, Chongxiao; Fuller, Alberta Lorraine; Pazdro, Robert; Sartori, José Roberto; Kim, Woo Kyun (Frontiers in Veterinary Science, 2020)
An experiment was conducted to evaluate the effect of different levels of inorganic copper and zinc on growth performance, intestinal permeability, intestinal lesion scores, oocyst shedding, antioxidant properties and bone quality in broilers challenged with Eimeria spp. A total of 360 d-old male Cobb broiler chickens were housed in floor cages for 12 days at the Poultry Research Center. At 12 days of age, birds were placed in grower Petersime batteries and distributed in a completely randomized design with 10 birds per cage, six replicates per treatment, and six treatments. There were six corn-soybean meal-based dietary treatments: non-challenged control (NC), challenged control (CC), 100 ppm Cu (100 Cu), 150 ppm Cu (150 Cu), 80 ppm Zn (80 Zn), and 100 ppm Zn (100 Zn). Broilers received the treatment diets for 9 days (12–20d). Birds, except NC, were challenged with Eimeria maxima (50,000 oocysts/bird), Eimeria tenella (50,000 oocysts/bird), and Eimeria acervulina (250,000 oocysts/bird) on 14d. On 20d, the growth performance was recorded, and one bird/cage was used for analysis of intestinal permeability, antioxidant properties and bone quality. Lesion score was recorded at 20 days of age in eight birds/cage. The means were subjected to ANOVA and, when significant, compared by Duncan's test. Intestinal permeability was significantly improved when birds received the 100 Zn diet (P < 0.05). In addition, lesion scores on duodenum were reduced when broilers received diets 150 Cu as compared to CC diet (P < 0.05). However, growth performance was not positively influenced by inclusion of inorganic minerals as compared to the NC diet. Furthermore, activity of superoxide dismutase and bone quality were not affected, whereas glutathione status was improved with mineral supplementation in all groups. This study showed that Cu and Zn supplementation improves intestinal integrity during the Eimeria spp. infection, suggesting that Cu and Zn supplementation would be a potential strategy to reduce detrimental effects of Eimeria infection in broilers.